1982
DOI: 10.1159/000241577
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Gestational Age and Fetal Activity Periods

Abstract: Cyclic patterns of active and quiet fetal activity were evaluated in 36 clinically normal gravidas between 27 and 42 weeks of gestation. All infants were subsequently delivered between 37 and 42 weeks of gestation, were clinically normal and of appropriate weight for gestational age. Active-quiet cycles occurred less frequently and were of longer duration with increasing gestational age. Regression analysis of the number of active-quiet cycles with gestational age yielded a correlation coefficient of 0.52 (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Dierken et al 6 in 1982 studied the number of quiet‐active cycles in regard to advancing gestational age. They found that the actual number of cycles showed a significant decrease with increasing gestational age.…”
Section: Various Factors Affecting Fetal Movementmentioning
confidence: 99%
“…Dierken et al 6 in 1982 studied the number of quiet‐active cycles in regard to advancing gestational age. They found that the actual number of cycles showed a significant decrease with increasing gestational age.…”
Section: Various Factors Affecting Fetal Movementmentioning
confidence: 99%
“…It serves multiple purposes for ensuring brain health, including memory consolidation, emotional processing, and most importantly, maintaining neural networks and synaptic plasticity (1)(2)(3)(4). Sleep begins to develop in early fetal life, during which it is described as an alternation in behavioral states (5)(6)(7). Poor quality sleep in the fetal and neonatal period is associated with lifelong developmental consequences.…”
Section: Introductionmentioning
confidence: 99%